Landscape Analysis of Financial Flows (LAFF): An inclusive method analyzing investment flows informs multi-stakeholders action plans and investment decision-making for sustainable development and resilient landscapes - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Tropenbos International (TBI) and EcoAgriculture Partners developed a participatory Landscape Analysis of Financial Flows (LAFF) method for multi-stakeholder partnerships (MSP) or individual actors (e.g., governments, non-governmental organizations, civil society organizations) seeking to advance sustainable landscape investments. The LAFF method helps participants develop a shared understanding of the landscape economy, identifying investment gaps and opportunities to meet locally-prioritized development objectives. LAFF has influenced policy, action plans, and investment decision-making in Ghana, Indonesia and Vietnam to support sustainability, climate action, and livelihoods.